FAKTOR-FAKTOR YANG MEMENGARUHI KEPUASAN DAN LOYALITAS KONSUMEN E-COMMERCE UNTUK PRODUK MAKANAN DAN MINUMAN - Muliasari, Risa Martha; Aulia, Anisa Nurina; Rizkina, Fitriana Dina; Nadiroh, Siti (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
Indonesia has the potential for a strong national economic base because the number of MSMEs, especially micro businesses, is very large and the labor absorption capacity is very large. One way to increase the capacity of micro and small businesses so they can upgrade to medium-sized businesses is to support and assist with online sales. This research aims to determine the factors that influence e-commerce consumer satisfaction and loyalty to food and beverage products. The research location is in Jember with the consideration that the district government program is in line with this research, namely strengthening the economy. Sampling technique with purposive sampling method. Respondent criteria are e-commerce users who have purchased food and beverage products in e-commerce. Data analysis used Spearman Rank Correlation. The research results show that the factors of intention to use, price, packaging safety, promotion and actual use are positively and significantly related to consumer satisfaction and loyalty to food and beverage products in e-commerce. The factor with the strongest relationship is actual use. The actual usage factor is reflected by the intensity with which consumers browse food and beverage products available on e-commerce applications very often. The suggestion from the results of this research is that marketing food and beverage products through e-commerce applications needs to display attractive visual or audio-visual content designs.